2020
DOI: 10.1186/s12909-020-02071-y
|View full text |Cite
|
Sign up to set email alerts
|

Medical professionalism in ophthalmology: design and testing of a scenario based survey

Abstract: Background Professionalism is hard to quantify but essential in medical practice. We present a survey tool for ophthalmologists that assessed professionalism using case-based scenarios in central Saudi Arabia. Methods Ophthalmologists (resident, fellows and consultants) participated in a web-based survey in 2015. Out of 44 attributes related to professionalism, experts selected 32 attributes with validity indices of ≥0.80. To evaluate these attributes, 51 scenario-based questions were developed and included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The survey was based on a previously validated scenario-based survey tool used by Alkahtani et al . [ 9 ] to evaluate medical professionalism in ophthalmology in Saudi Arabia. The survey language was slightly modified for grammar and spelling, and shortened to 33 questions with only 1 scenario-based question per professionalism attribute.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey was based on a previously validated scenario-based survey tool used by Alkahtani et al . [ 9 ] to evaluate medical professionalism in ophthalmology in Saudi Arabia. The survey language was slightly modified for grammar and spelling, and shortened to 33 questions with only 1 scenario-based question per professionalism attribute.…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, Alkahtani et al . [ 9 ] published a professionalism survey study in ophthalmology in central Saudi Arabia, based on the 35 professionalism attributes identified by Chandratilake et al . [ 7 ] The authors used 51 scenario-based questions, content validated by a panel of ophthalmology experts, to quantify the competency in professionalism among ophthalmology consultants and trainees by comparing their answers to the answers of the experts (identified as gold-standard).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the study showed that the majority of students have a positive attitude and perception toward professionalism [17]. Another two recent studies published in 2020 found a high level of professionalism among Saudi ophthalmologists [18] and Saudi general surgeons' residents [19] The study assessed the impact of incorporating the CanMEDS Competency Framework in the Saudi curriculum, residents' opinions regarding the CanMEDS competencies and its relationship with Clinical Leadership. The residents showed a satisfactory level of leadership skills and they embraced their acquisition of the CanMEDS competencies during their residency program.…”
Section: Morementioning
confidence: 97%
“…However, the changing nature of the organizational and social milieu in which medicine operates creates a dynamic situation where no definition has been universally agreed upon as definitive [ 3 , 6 ]. Despite these complexities, education for professionalism in medical school is crucial in the 21st century [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%